Dietary exposure assessment to perchlorate in the Taiwanese population: A risk assessment based on the probabilistic approach. (December 2020) - Chang, Wei-Hsiang; Chen, Hsiu-Ling; Lee, Ching-Chang
Abstract: Perchlorate is an endocrine-disrupting chemical (EDC) that contaminate various foodstuffs. Exposure to perchlorate may cause severe health problems, mainly thyroid dysfunction. However, information on perchlorate contamination of consumer foods in Taiwan is limited. This study investigated perchlorate levels in 310 food samples belonging to 12 food groups collected from Taiwanese markets. A probabilistic risk assessment was conducted to assess the related exposure to Taiwanese people. Perchlorate was detected in 65% of the samples and high levels were identified in certain plant-origin, fruit, and processed food samples. A probabilistic approach was used to estimate daily dietary dose (Monte Carlo–estimated 95th percentile dietary exposure [MCS 95]) by using the Taiwan National Food Consumption database for 14 sex/age groups. The highest and lowest average daily doses (ADDs) were in the age groups of >65 years (MCS 95 = 3.60/3.90 [male/female] μg/kg bw/day) and 16–18 years (MCS 95 = 1.70/1.47 [M/F] μg/kg bw/day), respectively. The 95th percentile of the hazard index of exposure to perchlorate of all sex/age groups far exceeded the tolerable daily intake (0.3 μg/kg bw/day) and reference dose (0.7 μg/kg bw/day) set by the European Food Safety Authority and US EPA, respectively, but it was lower than the provisional maximum tolerable daily intake (10 μg/kg bw/day) suggested by the Joint FAO/WHO Expert Committee on Food Additives. The intake quantity and concentrations of perchlorate from vegetables, fruits, and whole grains are the critical contributors for the ADDs and integrated risk of dietary exposure to perchlorate. Long-term exposure through diets should be considered, instead of focusing on individual EDC during dietary risk assessment in specific populations. Furthermore, cumulative risks for exposure to multiple contaminants, particularly those causing thyroid adverse effects, may be higher than that from perchlorate exposure alone. Graphical abstract: Image 1 Highlights: National dietary surveys and a probabilistic method were used to analyze ADD and HI. The relative high concentrations of perchlorate were found in foods of plant origin. Agricultural practice and fermentation processes affect perchlorate occurrences. Vegetable, fruit, and whole grain conduce to positive variance of perchlorate risk. All age-sex groups are at potential hazard risk via dietary intake to perchlorate.